The promise and performance of environmental conflict resolution - O'Leary, Rosemary, 1955-; Amsler, Lisa Blomgren, 1955- (Resources for the Future, 2003)
Environmental conflict resolution has been used since 1974 and an official part of policymaking since the mid-1990s. This book describes the kinds of disputes where it has been applied and critically investigates its record and potential, drawing on political science, anthropology and more.